THE COMPARISON OF TALKING STICK AND INVESTIGATION MODEL ON THE STUDENTS’ SPEAKING SKILL AT GRADE X STUDENTS OF SMK AL MA’SHUM SIDODADI IN ACADEMIC YEAR 2020/2021 - Dian Anggraini1 Datulina Ginting2 Paisal Manurung3,; Karimaliana4, Hamidah Sidabalok5 Dailami6 (Universitas Asahan, 2022)
ABSTRAK The objectives of this research is to at find out the differences between Talking Stick and Investigation Model on The Students’ Speaking Skill at Grade X students of SMK Al Ma’shum Sidodadi in Academic Year 2020/2021. This research had conducted in experiment design. There are two group, namely experimental group 1 and experimental group 2. Experimental group 1 had been taught by using Talking Stick Model, and experimental group 2 had been taught by using Investigation Model. The population of this research was taken from the grade X TKJ of SMK Al Ma’shum Sidodadi, and the sample were X TKJ-1 and X TKJ-2. The data has been collected from the pre-test and post-test value that worked by the students in experimental group 1 and experimental group 2. The data were analyzed by using t-test. The findings indicate that tvalue was lower than ttable (0,92 < 2,021). The result of this research that Ho is accepted which mention that teaching speaking by using Investigation model is not higher score than using Talking Stick model at grade X of SMK Al Ma’shum Sidodadi in Academic Year 2020/2021. This research shows that every model has different result. It is suggested to the teacher to use these model in teaching and learning process, so the students become more enjoyable in studying. Key words: Talking Stick, Investigation, Speaking.